Impact of US Economic Policy Uncertainty on Geopolitical Risk. Evidence from BRIC Economies - Arif, Imtiaz; Rawat, Amna Sohail; Shahbaz, Muhammad (Public Finance Quarterly, 2020)
This paper estimates the relationship between US economic policy uncertainty and geopolitical risk in the BRIC economies.1 Due to the assumption of a non-linear and asymmetric relation between US economic policy uncertainty and geopolitical risk of BRIC countries, a nonparametric estimation technique, Quantile on Quantile approach has been used for empirical analysis. The empirical results revealed that the relationship between the US economic policy uncertainty and geopolitical risk of BRIC economies is heterogeneous in nature. We noted that economic policy uncertainty in the US is negatively related to geopolitical risk in Chinese and Russian economies. However, for Indian and Brazilian economies US economic policy uncertainty is positively related to geopolitical risk. The outcomes of the study will be helpful for the investors and financial market players for taking investment decisions. It will also benefit the legislators and policymakers in making policies that could make their respective economies insulated from foreign policy risks.